Severe rhabdomyolysis in an infant due to fatty acid oxidation disorder: a case report - Amelie Krug; Pascale Perlot; Aurelie Empain; Catheline Vilain; Anne Monier; Kaoutar Tazi; Corinne De Laet (Journal of Medical Case Reports)
Abstract Background Rhabdomyolysis can develop from numerous etiologies, both acquired and hereditary. Consequences of rhabdomyolysis may be grave, therefore identifying and treating the etiology is crucial. Case presentation We herein report the occurrence of severe rhabdomyolysis in a previously healthy 14-month-old infant presenting to the emergency department with fever, hypotonia, and generalized discomfort. Analysis revealed extremely high creatine phosphokinase levels (> 100,000 UI/L). Metabolic myopathy was suspected, however, primary metabolic analyses were normal. Carnitine palmitoyltransferase II deficiency was diagnosed following genetic analysis, identifying a homozygous NM_000098.3, c.338C > T, p.[Ser113Leu] missense variant. Prophylactic measures were established to prevent relapse and genetic counseling provided for the sibship. Conclusion This case highlights the difficulty of diagnosing carnitine palmitoyltransferase II deficiency in an infant and the importance of genetic analysis to establish the diagnosis, despite a normal acylcarnitine profile.